2018
DOI: 10.1063/1.5006272
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of hydrogen in Fermi-level pinning in chalcopyrite and kesterite solar absorbers from first-principles calculations

Abstract: Understanding the impact of impurities in solar absorbers is critical to engineering high-performance in devices, particularly over extended periods of time. Here, we use hybrid functional calculations to explore the role of hydrogen interstitial (Hi) defects in the electronic properties of a number of attractive solar absorbers within the chalcopyrite and kesterite families to identify how this common impurity may influence device performance. Our results identify that Hi can inhibit the highly p-type conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 41 publications
7
23
0
Order By: Relevance
“…At high temperature during the thin-film growth or thermal annealing, the incorporation of the hydrogen or alkali metals at the interstitial sites will increase the Fermi level as they act as donors in p-type semiconductors. 60 The high Fermi level decreases the hole concentration and the formation of donor type defects as well (see Fig. 8c).…”
Section: Hydrogen and Alkali-metal Doping And Ag 2 Znsnsementioning
confidence: 88%
See 1 more Smart Citation
“…At high temperature during the thin-film growth or thermal annealing, the incorporation of the hydrogen or alkali metals at the interstitial sites will increase the Fermi level as they act as donors in p-type semiconductors. 60 The high Fermi level decreases the hole concentration and the formation of donor type defects as well (see Fig. 8c).…”
Section: Hydrogen and Alkali-metal Doping And Ag 2 Znsnsementioning
confidence: 88%
“…Alkali-metal elements may be less effective dopants due to their low solubility. 61 On the other hand, the previous calculations 60 have shown that the formation energies of H i in kesterites are low at p-type Fermilevel, suggesting high solubility of H in kesterites. We also noted that Son et al formed a S-Se grading in the current champion device 6 using H 2 S gas, which may introduce the H-doping unintentionally and be responsible for the high efficiency.…”
Section: Hydrogen and Alkali-metal Doping And Ag 2 Znsnsementioning
confidence: 90%
“…Hydrogen implantation in single-crystal CuInSe 2 (CIS) was responsible for a conductivity type conversion in the near-surface regions from an initially p-type material to n-type [5]. Fermi-level pinning in CIGS-based heterojunction devices was attributed to hydrogen and other interfacial defects, and led to a rollover of the open-circuit voltage limiting device efficiencies [6]. The introduction of hydrogen in CIS single crystals was also shown to improve the lattice structural stability by avoiding the formation of a radiation damage layer [7].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical activity of hydrogen in the ternary CIS and CuGaSe 2 (CGS) chalcopyrite compounds has been thoroughly studied in the past by first-principles approaches [6,10,11] based on density-functional theory [12,13]. For CIS the most recent study by Varley and coworkers [6] made use of the HSE06 hybrid functional [14][15][16], a choice that enabled a trusted reproduction of the experimental electronic gap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation